2017
DOI: 10.1089/mdr.2015.0356
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Carriage of Enterobacteriaceae Producing Extended-Spectrum Beta-Lactamases in Hospitalized Patients and Healthy Community Volunteers in Burkina Faso

Abstract: Extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) have been described worldwide, but few reports focused on Burkina Faso. To assess the prevalence of digestive carriage of such bacteria in the community and in the hospital, 214 fecal samples, 101 from healthy volunteers and 113 from hospitalized patients without digestive pathology, were collected in Bobo Dioulasso, Burkina Faso economic capital, during July and August 2014. Stool samples were screened using ESBL agar plates. Strains were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
14
16
2
Order By: Relevance
“…In the majority of the surveys, blaCTX-M-15 was the most common ESBL gene detected worlwide in animals and humans. [12,28,29] This result has been also found in Burkina Faso among human clinical samples and fecal carriage [30,31,32]. Then E. coli strains belonged majoritary to phylogroup A in our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the majority of the surveys, blaCTX-M-15 was the most common ESBL gene detected worlwide in animals and humans. [12,28,29] This result has been also found in Burkina Faso among human clinical samples and fecal carriage [30,31,32]. Then E. coli strains belonged majoritary to phylogroup A in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Then E. coli strains belonged majoritary to phylogroup A in our study. The majority of the african studies showed also a dominance of phylogroups A and B1 among healthy animals, derived meat, human clinical samples and human fecal carriage [12,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the research by Frickmann et al, 27.1% (13/48) of European military personnel with diarrhoea in Mali became colonized by ESBL-PE [ 23 ]. As for local populations, colonization rates of 22% have been reported for healthy volunteers in Burkina Faso [ 24 ] and 33% for healthy community children in Guinea-Bissau [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sadly, the current status of the diagnostic microbiology laboratory in LMIC would very rarely allow such support for AMS programs (25). Although point-prevalence surveys have demonstrated MDR bacteria have emerged in many LMIC (26)(27)(28), with striking heterogeneity, in humans as well as in animals (29), such data remain scarce: Many colleagues in LMIC work in an environment where they have no, or limited information about the prevalence of resistance to the antibiotics they use in common situations. Even in countries where surveillance is in place, updated, communication to prescribers is sub-optimal.…”
Section: The Specific Points To Condiser For Ams Programs In Lmicmentioning
confidence: 99%